Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.3201/eid0701.700146
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Studies of Fatal Cases in Outbreak of Hand, Foot, and Mouth Disease, Taiwan

Abstract: In 1998, an outbreak of enterovirus 71-associated hand, foot, and mouth disease occurred in Taiwan. Pathologic studies of two fatal cases with similar clinical features revealed two different causative agents, emphasizing the need for postmortem examinations and modern pathologic techniques in an outbreak investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 8 publications
4
24
0
1
Order By: Relevance
“…In contrast, cerebellar cortical lesions were observed in only 2 of 15 monkeys. The localization pattern of EV71-infected lesions was highly consistent with those observed in humans with severe EV71 encephalitis at autopsy [Lum et al, 1998;Wang et al, 1999;Chan et al, 2000;Wong et al, 2000;Shieh et al, 2001]. This finding suggests a similarity in the susceptibility of human and monkey CNS tissues to EV71 infection.…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, cerebellar cortical lesions were observed in only 2 of 15 monkeys. The localization pattern of EV71-infected lesions was highly consistent with those observed in humans with severe EV71 encephalitis at autopsy [Lum et al, 1998;Wang et al, 1999;Chan et al, 2000;Wong et al, 2000;Shieh et al, 2001]. This finding suggests a similarity in the susceptibility of human and monkey CNS tissues to EV71 infection.…”
Section: Discussionsupporting
confidence: 72%
“…Similar to the neurological manifestations in humans, cynomolgus monkeys display both pyramidal tract signs (flaccid paralysis) and extrapyramidal tract signs (including tremor and ataxia) with a broad viral antigen distribution that involves the spinal cord, brainstem, cerebellar cortex, dentate nuclei and cerebrum following intraspinal and intravenous inoculation of EV71 [22,23]. The neuropathological features are highly consistent with those observed in humans with severe EV71 encephalitis at autopsy [5,18,24-26], which is indicative of the similarity of the susceptibilities of human and cynomolgus monkey CNS tissues to EV71. EV71 exhibits a wider neurotropism than does poliovirus in cynomolgus monkeys, and wild-type strains, including those isolated from patients with fatal encephalitis or hand, foot, and mouth disease (HFMD), exhibit no marked differences with respect to neurovirulence after infection; thus, this monkey species may not be suitable for assessing the neurovirulence level of the virus [22,23].…”
Section: Reviewmentioning
confidence: 78%
“…Literature has reported that virus RNA and antibody can be detected at the affected area of brainstem encephalitis among patients with EV71 HFMD, suggesting that EV71 virus may be neurotropic [12,13]. The potential mechanism of CNS damage from EV71 infection is as follows: (1) EV71 viruses enter the blood circulation through throat or intestinal lymph nodes, resulting in the first viremia, and (2) viruses then invade and proliferate in reticuloendothelial tissue, deep lymph nodes, liver, spleen, and bone marrow and then enter the blood circulation, resulting in the second viremia [14].…”
Section: Pathophysiology Of Cns Damage From Ev71 Virus Infectionmentioning
confidence: 98%